Multipoint session types for a distributed calculus - Bonelli, Eduardo; Compagnoni, Adriana (2008)
Session types are a means of statically encoding patterns of interaction between two communicating parties. This paper explores a distributed calculus with session types in which a number of fixed sites interact. The reduction schemes describing the operational semantics satisfy the locality principle: at most one site is involved. Both session engagement and data communication are local and asynchronous. Furthermore, our setting is a natural one in which the novel notion of multipoint session types, sessions in which more than two parties may be involved, can be introduced.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Trustworthy Global Computing : Third Symposium, TGC 2007, Sophia-Antipolis, France, November 5-6, 2007, Revised Selected Papers. Berlín : Springer, 2008. (Lecture Notes in Computer Science ; 4912), pp. 240-256
Keywords: CÁLCULO DISTRIBUIDO; CODIFICACIÓN